The Holy Man Based on a Story by Rajshekhar 'Parashuram' Basu - Ray, Satyajit; Roy, Soumendu; Ghosh, Charuprakash; Ghosh, Rabi; Mukherjee, Prasad (The Satyajit Ray Blu-ray Collection, 2014)
A witty romantic comedy full of quick dialogue and smart insight, the story follows the fantastical tales surrounding an Indian holy man who claims to have lived for centuries, meeting Plato, Jesus, and Buddha. Wrapped up in his followers is Gurupada (Prasad Mukherjee), an older widower depressed from losing his wife and looking for something to fill the void. When Gurupada's youngest daughter Buchki (Gitali Roy) and the young man who is hopelessly in love with her, Satiya (Satindra Bhattacharya), become enraptured by the teachings of the holy man as well, Gurupada finally begins to see that the holy man he has put so much faith in may be nothing more than a charlatan. Defined by an unusual lightness of touch from director Ray, the lighthearted "Mahapurush" is nevertheless a cleverly crafted and subversive indictment of post-war India, even as it takes on the guise of a brief and charmingly absurd love story and comedy of manners. [www.theaterbyte.com]